2017
DOI: 10.1186/s12864-017-3727-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of glucose-6-phosphatase encoding genes in vertebrate lineages: towards a better understanding of the functions of multiple duplicates

Abstract: BackgroundGlucose-6-phosphate (G6pc) is a key enzyme involved in the regulation of the glucose homeostasis. The present study aims at revisiting and clarifying the evolutionary history of g6pc genes in vertebrates.Results g6pc duplications happened by successive rounds of whole genome duplication that occurred during vertebrate evolution. g6pc duplicated before or around Osteichthyes/Chondrichthyes radiation, giving rise to g6pca and g6pcb as a consequence of the second vertebrate whole genome duplication. g6p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
3
6
0
Order By: Relevance
“…treatment resulted in an increased activity of Gsase, as well as an increased mRNA abundance of GK, GLUT2, GSase and Kir6.x‐like. Furthermore, the increase observed in the values of G6Pase is in agreement with the effect observed in the same brain region after feeding rainbow trout with a carbohydrate‐enriched diet . Strikingly, GK activity did not follow changes indicated by its mRNA abundance.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…treatment resulted in an increased activity of Gsase, as well as an increased mRNA abundance of GK, GLUT2, GSase and Kir6.x‐like. Furthermore, the increase observed in the values of G6Pase is in agreement with the effect observed in the same brain region after feeding rainbow trout with a carbohydrate‐enriched diet . Strikingly, GK activity did not follow changes indicated by its mRNA abundance.…”
Section: Discussionsupporting
confidence: 86%
“…treatment with glucose enhanced CART mRNA abundance in the telencephalon of catfish and zebrafish (ie, comparable responses to those previously described in other glucosensing areas in fish, such as the hypothalamus and hindbrain) . Second, the mRNA abundance of g6pcb2b , a gene expressing the enzyme glucose 6‐phosphatase (G6Pase) involved in glucose metabolism, increased in the telencephalon of rainbow trout fed with a carbohydrate‐enriched diet . The function of these hypothetical glucosensing mechanisms in the telencephalon might relate to metabolic control of food intake via either homeostatic or hedonic (reward) pathways.…”
Section: Introductionsupporting
confidence: 67%
“…When more than 20% of FM is substituted by digestible carbohydrates in the diet, they typically display a decrease in growth and a persistent postprandial hyperglycemia. Different hypotheses have been proposed to explain this phenomena (Kamalam et al, 2017) and among them, is the lack of inhibition in the last step of the hepatic gluconeogenesis (Marandel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although recent studies suggested that fish, especially carnivorous fish, lacked the ability to regulate gluconeogenesis (45)(46)(47)(48), the expression of key genes involved in gluconeogenesis in mandarin fish after IP of leptins were decreased as in mammals. In rat, leptin was reported to reduce hepatic glucose production by decreasing the synthesis of the key enzyme of gluconeogenesis (49).…”
Section: Discussionmentioning
confidence: 99%